Potability of Well Water in Falluja City ,Iraq. - Al_nima, B.A.B.; Saadalla, H. A.A.; Al__Al wani, M. A.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
The Falluja residents had resorted to the underground water as an alternative to the surface waters of the Euphrates river passing near the city, through digging wells inside gardens of Mosques in the city during spring 2005. The present study aims to indicate the quality of these waters and demonstrates the extent of their suitability for drinking . For this purpose, 21 randomly distributed wells were chosen during August 2005. The water characters were measured ; the average values of 21 wells were as follows : Water temp .(22.6C Ù’ â—Œ ) , EC (4,11 msem .), pH (7.15 ) and concentration of cations : Na (439mgł) ;K (275mgł) ; Li (0,28mgł), Ba (15.2 mgł) and (133mgł). These character is ties were compared with the allowded limits presented by concerned authorities. The results of the study indicated the absence of any relationship between temperature and depth of the well. Also waters of all studied wells were not suitable for drinking as the EC , K and Ba concentrations were higher than the allowded limits . In addition, Na and Ca concentration of some wells exceeded the allowded limits.